Analisis Kepraktisan E-module Berbasis Inkuiri Terbimbing pada Materi Tekanan Zat Cair - Siti Muslikatin; Bowo Sugiharto; Meti Sugiharto (Universitas Sebelas Maret, 2025)
This study aims to determine the practicality of an e-module based on guided inquiry on the material of liquid pressure which was developed to empower student’science process skills. This type of research uses the research and development (R&D) method using the Four-D model. The practicality of the E-module is assessed through a questionnaire of teacher and student responses after using the e-module in the learning process. The initial test subjects consisted of 2 science teachers and 32 grade IX students at a state MTs. Data were analyzed descriptively quantitatively. The results of the study showed that the developed e-module obtained an average practicality score of 95% which is included in the “very practical” category. This shows that the guided inquiry based e-module on the subject of liqquid pressure is suitable for use as a learning medium in the classroom. The practicality of the e-module is supported by ease of use, understandability of the contents of thr e-module, suitability with guided inquiry steps, empowering science process skills, attractive appearance, and time of use, thus making it easier for students to understand the concept of liquid pressure independently and in depth. Thus, this e-module is recommended as an effective alternative learning resource to improve the quality of physics learning.